Accounting for price-level changes--theory and procedures - Gynther, Reginald Sydney (Pergamon international library of science, technology, engineering, and social studies., 1966)
Accounting for Price-Level Changes: Theory and Procedures shows the importance of taking actions to incorporate the effects of changing prices into each firms accounting systems, and encourage the firms to treat this incorporation as a normal routine.